Protective effects of dioscin against fructose-induced renal damage via adjusting Sirt3-mediated oxidative stress, fibrosis, lipid metabolism and inflammation. (1st March 2018) - Qiao, Yujie; Xu, Lina; Tao, Xufeng; Yin, Lianhong; Qi, Yan; Xu, Youwei; Han, Xu; Tang, Zeyao; Ma, Xiaodong; Liu, Kexin; Peng, Jinyong
Graphical abstract: Highlights: Dioscin showed protective effect against fructose-induced kidney injury in rats. Dioscin improved oxidative damage and renal fibrosis caused by fructose in rats. Dioscin improved lipid metabolism and inflammation caused by fructose in rats. Dioscin up-regulated the expression level of Sirt3. Abstract: In the present work, the effects and possible mechanisms of dioscin, one natural product from the famous vegetable Dioscoreae rhizoma (Shanyao in Chinese), against high fructose-induced renal injury in rats were tested. The results showed that dioscin significantly restored fructose-induced renal injury by decreasing the levels of Cr, BUN, and rehabilitating histopathological changes. In addition, dioscin markedly adjusted the levels of MDA, SOD and GSH-Px, reduced ROS level in renal tissue, and decreased the levels of TG, FFA, α-SMA and COL1A. Mechanistic study showed that dioscin significantly up-regulated the expression levels of Sirt3, SOD2, and then suppressed inflammation by decreasing the expression levels of NF-kB, HMGB1, c-Jun, c-Fos, COX2, TNF-α, IL-1β and IL-6. Furthermore, dioscin-caused high levels of Sirt3 and SOD2 attenuated oxidative stress by regulating the expression levels of Nrf2, GST, Keap1, regulated lipid metabolism by controlling the expression levels of SREBP-1c, SCD-1, FASn, ACC, CPT1, and adjusted TGF-β1/Smad signal to inhibit renal fibrosis. In summary, dioscin showed protective effects against fructose-induced renal damage via adjusting Sirt3-mediated oxidative stress, renal fibrosis, lipid metabolism and inflammation, which should be considered as one candidate to treat renal injury in the future. We also suggest that the patients with renal injury can take more Shanyao for the therapy and treatment.